BIAL 15(2), 2005 páginas 7 e 8 - LOPES, Maria do Rosário Vigeta; SANTOS, Cecilia Cristina Marques dos; RIGO, Karina Marques (Boletim do Instituto Adolfo Lutz - BIAL, 2006)
Figura 1 - Curva de calibração para PA Figura 2 - Curva de calibração para PB